Honour Crimes: Transdisciplinary Issue - Smolík, Josef (Kultura-Społeczeństwo-Edukacja, 2016)
This article introduces so-called honour crimes (sometimes termed honour based violence), which tends to occur within Islamic communities located within ‘host’ countries in Europe. It is a very specific type of crime, which takes place in the family setting in Muslim families, and is in direct contradiction with the democratic values and legal systems of Western states. The aim of this paper is to introduce the issue and illustrate it in relation to selected cases. It offers both an evaluative and descriptive stance.